LbDSF, the Lysobacter brunescens Quorum-Sensing System Diffusible Signaling Factor, Regulates Anti- Xanthomonas XSAC Biosynthesis, Colony Morphology, and Surface Motility - Ling, Jun; Zhu, Runjie; Laborda, Pedro; Jiang, Tianping; Jia, Yifan; Zhao, Yangyang; Liu, Fengquan (Frontiers in Microbiology, 2019)
Lysobacter species are emerging as novel sources of antibiotics, but the regulation of these antibiotics has not been thoroughly elucidated to date. In this work, we identified a small diffusible signalling factor (DSF) molecule (LbDSF) that regulates the biosynthesis of a novel Xanthomonas-specific antibiotic compound(s) (XSAC) in Lysobacter brunescens OH23. LbDSF was isolated from the culture broth of L. brunescens OH23, and the chemical structure of the molecule was determined by NMR and MS. The LbDSF compound induced GUS expression in a reporter strain of Xanthomonas campestris pv. campestris FE58, which contained the gus gene under the control of a DSF-inducible engXCA promoter. LbDSF production was found to be linked to the enoyl-CoA hydratase RpfF and dependent on the two-component regulatory system RpfC (hybrid sensor histidine kinase)/RpfG (response regulator), and LbDSF production was increased 6.72 times in the ΔrpfC compared to wild-type OH23. LbDSF-regulated XSAC production was dramatically decreased in ΔrpfF, ΔrpfC, and ΔrpfG. Additionally, a significant reduction in surface motility and a number of changes in colony morphology were observed in the ΔrpfF, ΔrpfC, and ΔrpfG compared to the wild-type OH23. The exogenous LbDSF significantly increased XSAC production in wild-type OH23 and recovered the XSAC biosynthetic ability in ΔrpfF. Taken together, these results showed that LbDSF is a fatty acid-derived DSF that positively regulates XSAC biosynthesis, cell morphology, and surface motility. Moreover, the RpfC/RpfG quorum sensing signal transduction pathway mediates XSAC biosynthesis. These findings may facilitate antibiotic production through genetic engineering in Lysobacter spp.